Systematic review of therapeutic nipple‐sparing versus skin‐sparing mastectomy. Issue 2 (19th December 2018) - Agha, R. A.; Al Omran, Y.; Wellstead, G.; Sagoo, H.; Barai, I.; Rajmohan, S.; Borrelli, M. R; Vella‐Baldacchino, M.; Orgill, D. P.; Rusby, J. E.
Abstract : Background: The use of nipple‐sparing mastectomy (NSM) is increasing, despite unproven oncological safety in the therapeutic setting. The aim of this systematic review was to determine the safety and efficacy of NSM compared with skin‐sparing mastectomy (SSM). Methods: A literature search of all original studies including RCTs, cohort studies and case–control studies comparing women undergoing therapeutic NSM or SSM for breast cancer was undertaken. Primary outcomes were oncological outcomes; secondary outcomes were clinical, aesthetic, patient‐reported and quality‐of‐life outcomes. Data analysis was undertaken to explore the relationship between NSM and SSM, and preselected outcomes. Heterogeneity was assessed using the Cochrane tests. Results: A total of 690 articles were identified, of which 14 were included. There was no statistically significant difference in 5‐year disease‐free survival and mortality for NSM and SSM groups, where data were available. Local recurrence rates were also similar for NSM and SSM (3·9 versus 3·3 per cent respectively; P = 0·45). NSM had a partial or complete nipple necrosis rate of 15·0 per cent, and a higher complication rate than SSM (22·6 versus 14·0 per cent respectively). The higher overall complication rate was due to the rate of nipple necrosis in the NSM group (15·0 per cent). Conclusion: In carefully selected cases, NSM is a viable choice for women with breast cancer who need to have a mastectomy. More research is needed to help further refine which surgical approaches to NSM optimize outcomes. Abstract : The objective of this systematic review was to determine the safety and efficacy of nipple‐sparing mastectomy (NSM) as compared with skin‐sparing mastectomy (SSM). In carefully selected cases, NSM is a viable choice for women with breast cancer needing to undergo mastectomy. More research is needed to help further refine the evidence on which surgical approaches to NSM optimize outcomes. Nipple‐sparing can be a safe choice